2011
DOI: 10.1128/aem.01885-10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Multidrug-Resistant Salmonella enterica Strains Associated with Cattle at Harvest in the United States

Abstract: The prevalence and diversity of multidrug-resistant (MDR) Salmonella enterica strains associated with cattle at harvest in the United States were examined. Hides and carcasses of cattle were sampled at processing plants (n ‫؍‬ 6) located in four geographically distant regions from July 2005 to April 2006. The mean prevalences of Salmonella on hides, preevisceration carcasses (immediately after hide removal), and postintervention carcasses (in the chiller and after the full complement of interventions) were 89.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 76 publications
(94 reference statements)
3
43
0
Order By: Relevance
“…Similar study in Venezuela revealed that 36.3% of bovine hides and 7.2% of the corresponding carcasses after evisceration were positive for this pathogen (16). In the USA, Salmonella-positive samples were identified, depending on the season, on 86.1% -93.8% hides (spring and summer) and on 44.2% -55.3% carcasses (spring and winter), respectively (6). In Europe, the percentage of contaminated bovine hides varied depending on the author, place of sampling, and season of the year.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar study in Venezuela revealed that 36.3% of bovine hides and 7.2% of the corresponding carcasses after evisceration were positive for this pathogen (16). In the USA, Salmonella-positive samples were identified, depending on the season, on 86.1% -93.8% hides (spring and summer) and on 44.2% -55.3% carcasses (spring and winter), respectively (6). In Europe, the percentage of contaminated bovine hides varied depending on the author, place of sampling, and season of the year.…”
Section: Discussionsupporting
confidence: 53%
“…To assess the routes of transmission and molecular relatedness of Salmonella isolates along the food chain, usually the pulsed field gel electrophoresis (PFGE) method is applied due to its discriminatory power and reproducibility (6,21). This approach allows establishing routes and sources of carcass contamination with these pathogenic bacteria at abattoirs and at the meat level.…”
Section: Introductionmentioning
confidence: 99%
“…Brichta-Harhay et al (58) demonstrated that 3GC r Salmonella spp. were a subpopulation of generic Salmonella in beef processing environments using extensive antimicrobial susceptibility analysis of generic Salmonella isolates (i.e., isolates of colonies grown on media permissive for Salmonella regardless of antimicrobial susceptibility), but the concentrations of 3GC…”
Section: Gcmentioning
confidence: 99%
“…Arthur and colleagues (20) isolated Salmonella (n ϭ 18) from subiliac and superficial cervical lymph nodes and reported resistance among 22.2% (n ϭ 4) of isolates, with 16.7% (n ϭ 3) demonstrating MDR phenotypes. Salmonella antimicrobial resistance poses a challenge to human medicine, as ceftriaxone, an extended-spectrum cephalosporin, is a common choice for treating salmonellosis in children (38). Adult salmonellosis is often treated with nalidixic acid and ciprofloxacin, a quinolone and fluoroquinolone, respectively (38).…”
Section: Fig 1 Partial Dendrogram Representing the Distribution Of Samentioning
confidence: 99%